The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ijch.201700050
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Iron Catalyzed Oxidation Reactions of Organic Compounds

Abstract: Iron-catalyzed oxidation reactions have been increasingly investigated in the past two decades and have seen a major increase in research activity. This review article demonstrates the vigorous research activities in the field based on examples from the most recent literature. Catalyst systems are discussed that are active in the oxygenation of alkanes and alkenes to obtain alcohols, ketones or epoxides. Iron-catalyzed oxidation of alcohols to the corresponding carbonyl units are also included. Enantioselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 210 publications
1
6
0
Order By: Relevance
“…Iron-based catalysts or co-catalysts are well-introduced and famous species for catalyzing oxidation reactions in organic chemistry. ,, Iron and other transition metals mainly catalyze oxidation through the redox property. , Iron oxide is one of the famous species and effective catalysts for the oxidation reactions of organic compounds such as alcohols, , alkenes, , asphaltenes, ,, and crude oils. , In addition, iron oxides can be easily applied in industry because of their relatively low cost. Therefore, in this work, we focus on iron oxide (Fe 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iron-based catalysts or co-catalysts are well-introduced and famous species for catalyzing oxidation reactions in organic chemistry. ,, Iron and other transition metals mainly catalyze oxidation through the redox property. , Iron oxide is one of the famous species and effective catalysts for the oxidation reactions of organic compounds such as alcohols, , alkenes, , asphaltenes, ,, and crude oils. , In addition, iron oxides can be easily applied in industry because of their relatively low cost. Therefore, in this work, we focus on iron oxide (Fe 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that the anionic ligand of iron had a crucial effect on the alcohol oxidation. In the case of [NO 3 – ] and [Cl – ], we suspected that in situ generation of NO x and hypochlorous acid was responsible for the menthol oxidation . Nevertheless, this finding suggested that the FeBr 3 /H 2 O 2 system was less likely to involve the high-valent iron species for the alcohol oxidation (entries 9 and 10).…”
mentioning
confidence: 98%
“…The alternative of employing iron-based catalysts and hydrogen peroxide as oxidant is gaining importance for the liquid phase oxidation of glycerol under mild conditions (base-free, ambient temperature, and atmospheric pressure). , Crotti and Farnetti performed the glycerol oxidation in an acetonitrile/water mixture using homogeneous iron complexes associated to the tridentate ligand bis­(2-pyridinylmethyl)­amine (BPA) as catalyst. They reported that high selectivity toward DHA or formic acid could be achieved by tuning operating conditions.…”
Section: Clean Catalytic Oxidation Of Alcoholsmentioning
confidence: 99%